2009
DOI: 10.1002/app.31459
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of surface friction of natural rubber film coated with PMMA particle: Effect of particle size

Abstract: The friction coefficient of the sulphurprevulcanized natural rubber (SPNR) film could be effectively reduced by deposition of poly(methyl methacrylate) (PMMA) particles. The nanoscale surface roughness of rubber, determined by atomic force microscope, was directly proportional to the particle size of PMMA particle at 12% surface coverage (Cs). The %Cs and surface roughness of the modified SPNR increased, while the friction coefficient decreased, with increasing PMMA latex concentration and immersion time. By u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…The decrease of coefficient of friction clarified that the presence of PMMA/PEI nanoparticles on the SPNR surface would potentially reduce the friction force of the rubber sheet. Anancharungsuk et al 18 found that the friction coefficient of SPNR-g-PAAm sheets coated with lean PMMA particles decreased with the size of PMMA particles and C s values. At 626 nm of PMMA particles and the C s value of 36.4%, the friction coefficient can be reduced to $ 1.2 or 45% reduction.…”
Section: Coefficient Of Friction Of Pmma/pei-coated Spnr Sheetsmentioning
confidence: 98%
“…The decrease of coefficient of friction clarified that the presence of PMMA/PEI nanoparticles on the SPNR surface would potentially reduce the friction force of the rubber sheet. Anancharungsuk et al 18 found that the friction coefficient of SPNR-g-PAAm sheets coated with lean PMMA particles decreased with the size of PMMA particles and C s values. At 626 nm of PMMA particles and the C s value of 36.4%, the friction coefficient can be reduced to $ 1.2 or 45% reduction.…”
Section: Coefficient Of Friction Of Pmma/pei-coated Spnr Sheetsmentioning
confidence: 98%
“…S6(c)). Small size of PMMA-SiNPs(TMC) (435 nm) facilitated fast diffusion of particles towards SPNR surface [34] and, hence, the longer the immersion time the higher the Cs values.…”
Section: Analysis Of Spnr Film Coated With Pmma-sinps(tmc) Particlesmentioning
confidence: 99%
“…The fiber distribution within the second RVE is generated using the random sequential adsorption algorithm , which ensures a random and homogeneous distribution of the sepiolite fibers. The diameter d of fiber is 0.1 μm .…”
Section: Computational Micromechanics Modelmentioning
confidence: 99%
“…It is assumed that the RVE is periodic and thus the microstructure of either material can be obtained by translating the square RVE along horizontal and vertical directions. The fiber distribution within the second RVE is generated using the random sequential adsorption algorithm [22][23][24], which ensures a random and homogeneous distribution of the sepiolite fibers. The diameter d of fiber is 0.1 lm [25,26].…”
Section: Generation Of the Rvementioning
confidence: 99%